2022
DOI: 10.1109/tgrs.2022.3202490
|View full text |Cite
|
Sign up to set email alerts
|

HapkeCNN: Blind Nonlinear Unmixing for Intimate Mixtures Using Hapke Model and Convolutional Neural Network

Abstract: This paper proposes a blind nonlinear unmixing technique for intimate mixtures using the Hapke model and convolutional neural networks (HapkeCNN). We use the Hapke model and a fully convolutional encoder-decoder deep network for the nonlinear unmixing. Additionally, we propose a novel loss function that includes three terms; 1) a quadratic term based on the Hapke model, that captures the nonlinearity, 2) the reconstruction error of the reflectances, to ensure the fidelity of the reconstructed reflectance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In the first step, the encoder was used to linearly estimate the endmember and its corresponding abundance fraction, and in the second step, the bilinear model was used to improve the estimation results of the first part. A blind nonlinear unmixing technique based on the Hapke model and convolution neural network (HapkeCNN) was proposed in [37]. It was trained by a loss function including a quadratic term based on the Hapke model, the reconstruction error of the reflectances, and a minimum volume total variation (TV) term.…”
Section: Model-guided DL Methodsmentioning
confidence: 99%
“…In the first step, the encoder was used to linearly estimate the endmember and its corresponding abundance fraction, and in the second step, the bilinear model was used to improve the estimation results of the first part. A blind nonlinear unmixing technique based on the Hapke model and convolution neural network (HapkeCNN) was proposed in [37]. It was trained by a loss function including a quadratic term based on the Hapke model, the reconstruction error of the reflectances, and a minimum volume total variation (TV) term.…”
Section: Model-guided DL Methodsmentioning
confidence: 99%
“…Two real hyperspectral remote sensing images were further applied to evaluate the performance of the proposed FTUPSO in practical scenarios. Due to the absence of ground truth, two quantitative metrics (i.e., RE and SRE) defined in (23) and (24) and qualitative experimental results including endmember curves and abundance maps were adopted to compare the overall unmixing accuracy of the methods. In addition, the execution time for each method was provided.…”
Section: Real Hyperspectral Data Experimentsmentioning
confidence: 99%
“…In [22] the nonlinear mixing effects were modeled by two fully connected hidden layers with a 3D convolutional neural network (CNN) capturing the spatial-spectral information of HSI. To enhance physical interpretability, a fully convolutional deep AE network was combined with the Hapke model in [23], yielding better unmixing results for intimate mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Deep autoencoder architectures have been developed that utilize the PPNM to reconstruct the input hyperspectral image [27], [28]. In [29], it was demonstrated that the endmembers of nonlinear datasets can be accurately estimated through the use of deep autoencoder architectures.…”
Section: Introductionmentioning
confidence: 99%